Ox draught power and agricultural transformation in northern Zambia - Francis, P.A. (Elsevier, 1988)
Discusses the conditions under which draft oxen have been adopted in Mpika District, Zambia, their impact on resource use and productivity, and the implications for further agricultural change. Assesses the effect of oxenization on labour allocation and the timeliness of key operations.